A vulnerabilidade dos 20% mais pobres do Brasil e o mercado de trabalho no período 2004-2014 - Soares, Laís Cristina (2017)
This study aims to analyze the insertion of the poorest 20% of Brazil in the labor market and to present the evolution of their insertion in the period 2004-2014, in order to verify if there was a reduction of the vulnerability and the decent work deficit of this part of the Population. It started from the fact that the insertion of the poorest in the labor market is marked by occupational instability. The theoretical framework was based on the concepts of vulnerability of work and decent work. The selection of the indicators to analyze the evolution in the labor market was made based on the coherence and adherence to the theoretical foundations and the availability of data from the National Household Sample Survey (PNAD). It is concluded that, despite the social advances of the period and the improvement of labor market indicators in the Brazilian average, the employed population among the poorest 20% did not show significant changes in their insertion in the Brazilian labor market, maintaining a high deficit Decent work